Evaluation of learning in physical education: A bibliometric analysis and future trends - Hadiwinarto; Gheorghe Balint; Feby Elra Perdima (Journal Sport Area, 2022)
This study analyzes academic research published in Scopus on the evaluation of physical education learning. This study focuses on the following research questions: (1) How is the productivity of educational evaluation publications in physical education developed using the Scopus database? (2) What are the most influential journals, authors, and articles in the field of educational evaluation in physical education learning? (3) What are the keywords that often appear in the field of educational evaluation in physical education learning in the Scopus database?. The search results show that research is "evaluation" AND "learning" AND "physical education". Search Results (515 result documents) which began to be published in the Scopus database from 2011-2021. Furthermore, the researchers filter the types of documents which are only limited to journal articles, so the number of documents found is 188 documents. Based on publications in the Scopus database, the findings reveal that: the number of publications is increasing, although there is an up and down trend from year to year; most publications are written by researchers residing in several states and universities. From the emergence of keywords, the topic of assessment evaluation in physical education becomes an interesting thing to discuss. This analysis can provide knowledge about research development in aspects of evaluation and physical education and can be a source of data for teachers, lecturers, schools, universities, and the world of education. For future researchers, they can map these points by analyzing the databases of Website of Science and other publishers. Further researchers can also carry out scientometric analysis by combining two databases (Scopus and WoS) using ScientoPy and can continue with mapping until the end of 2022 and can also be a reference by seeing what points are interesting and have not been reviewed by previous researchers.